Securing superior properties of composite (PP+WF) through central composite design - Karim, A.N. Mustafizul; Khalid, Nor A. B.; Ismail, Raja N. H. R.; Haque, Mahbubul; Begum, Shahida (Trans Tech Publications Ltd., Switzerland, 2012)
Due to numerous attractive properties, use of composites is in increasing trend. Efforts are being made to develop new composites securing their useful properties at optimum level for more demanding applications. The purpose of this project is to optimize the mechanical properties of composite (polypropylene + wood fiber) using Central Composite Design (CCD) technique. Accordingly experiments were conducted to develop mathematical models in terms of three process parameters - composition (percentage of PP and wood fiber), injection pressure (bar), and time (second) for functional characteristics such as tensile strength and water absorption. Design expert software was used for convenience to carry out the analysis with a view to identifying the optimum level of the processing parameters for securing the desirable properties of the composite.